Transforming conflict: analyzing the impact of UN security council resolution 2334 on human security in Israel-Palestine - Edwin Tri Putra; Pratama Dahlian Persadha; Suhardi Suhardi (Institute Of computer Science (IOCS), 2024)
The United Nations Security Council's Resolution 2334 effectively puts an end to the Palestinian-Israeli conflict. This resolution explicitly calls for the annexation of settlements, the relocation of Israeli settlements, the destruction of homes, and the transfer of Palestinian populations. Peace and the defusing of tensions in the area are the primary aims of the resolution. The expected tranquil situation is likely to have an effect on individual safety. Therefore, the perspective of human security will be used to analyse UN Security Council Resolution 2334. This paper concludes that UN Security Council Resolution 2334 satisfies the indicator of human security approach because it requires Israel and Palestine to comply with international humanitarian law, the opinion of the International Court of Justice, the Quartet Roadmap, and numerous prior resolutions. All of the aforementioned treaties, conventions, and agreements are designed to safeguard citizens' financial, nutritional, medical, scholastic, occupational, civic, and political rights. However, in reality, there were several issues with this agreement, and Israel often ignored it. In this descriptive qualitative research, a literature review serves as the major method of information collecting.